2013
DOI: 10.1108/jpbafm-25-03-2013-b003
|View full text |Cite
|
Sign up to set email alerts
|

City responses to economic downturns 2003 to 2009: Statistical and textual analyses of comprehensive annual financial reports

Abstract: This paper analyzes the impact of economic downturns on the revenue and expense sides of city financing for the period 2003 to 2009 using a convenience sample of the audited end of year financial reports for thirty midsized US cities. The analysis focuses on whether and how quickly and how extensively revenue and spending directions from past years are altered by recessions. A seven year series of Comprehensive Annual Financial Report (CAFR) data serves to explore whether citiesʼ revenues and spending, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…In the literature, there have been various studies on local government financial resilience [1,[10][11][12]14,[20][21][22][23][24][25][26][27][28], but the concept of fiscal resilience is lacking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, there have been various studies on local government financial resilience [1,[10][11][12]14,[20][21][22][23][24][25][26][27][28], but the concept of fiscal resilience is lacking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the approval ratings for the ruling party was high, which served as an impetus for the Parliament to pass the budget. Many studies have investigated state or municipal responses to economic downturns or recessions (Darvas, 2010;Sacco and Busche e, 2013;Campbell and Sances, 2013;Cary and Bush, 2018). Poterba (1994) demonstrated that, facing economic downturn and fiscal crises, state fiscal institutions adjust to address budget deficits.…”
Section: Timeliness and Frequency Of Supplementary Budgets During Covid-19mentioning
confidence: 99%